Overview of Hemoglobin Levels and Nutritional Status Based on Body Mass Index (BMI) and Upper Arm Circumference (LLA) Indicators in Foster Families in Uteunkot Village, Muara Dua District, Lhokseumawe in 2021 - Mardiati; Noviana Zara; Anna Millizia (Arkus, 2022)
Hemoglobin is a protein found in red blood cells. Hemoglobin levels that are less than normal or anemia can cause complications in the form of fatigue and stress on the body's organs. Nutritional status is one of the factors that can affect hemoglobin levels. Measurement of nutritional status can be done through several methods including anthropometry and clinical laboratories. Among these methods, the most frequently used in the field is anthropometry using body mass index (BMI) and upper arm circumference (LLA). This study aims to determine the hemoglobin level and nutritional status of the assisted families located in Uteunkot Cunda Village, Lhokseumawe. This study is a descriptive study with a cross-sectional approach to determine the description of hemoglobin levels and nutritional status based on indicators of Body Mass Index and Upper Arm Circumference in the fostered family. The sampling technique used is total sampling with a total of 79 respondents. The results obtained were the average hemoglobin level of the respondents was 12.34 g/dL in the normal category. Nutritional status based on Body Mass Index, most respondents were in normal nutritional status as many as 27 respondents (34.2%). The most nutritional status based on upper arm circumference was malnutrition, namely 55 respondents (69.6%).